Omega-3 PUFAs’ efficacy in the therapy of coronary artery disease combined with anxiety or depression: a meta-analysis - Gui, Yiwei; He, Dongyu; Li, Junwei; Zhao, Haibin (Frontiers in Psychiatry, 2024)
Objective The evidence demonstrates that omega-3 polyunsaturated fatty acids (omega-3 PUFAs) protect the cardiovascular system and alleviate anxious or depressive situations. We conducted a meta-analysis to evaluate the effectiveness of omega-3 PUFAs in the treatment of anxiety or depressive states in patients with coronary artery disease. Methods This meta-analysis analyzed data from randomized controlled trials to determine the efficacy of omega-3 PUFAs alone or in combination with conventional psychotropic medications in coronary artery disease patients suffering from anxiety or depression. Primary outcomes included changes in depression scores, the Beck Anxiety Inventory (BAI) scores, and the omega-3 index. Results Included were 6 trials involving 2,570 participants. Compared to controls,omega-3 PUFAs did not improve depression or anxiety {depression: [SMD=0.09 (95% CI: -0.07, 0.26)], anxiety [BAI: SMD=0.07 (95% CI: -0.17, 0.32)]}; For the results of the subgroup analyses, analyzed by different types of depression scales, four studies used the HAMD scale [SMD=0.19 (95% CI: -0.20, 0.58)]; 5 studies used the BDI-II scale [SMD=0.01 (95% CI: -0.07, 0.09)], all of which indicated no decrease in depression scale scores; analyzed by different types of intervention, 3 studies used the omega-3 PUFAs group [SMD=0.24 (95% CI: -0.26, 0.74)]; 2 studies used sertraline + omega-3 PUFAs [SMD=-0.08 (95% CI: -0.46, 0.31)], and the omega-3 index was elevated [SMD=1.33 (95% CI: 0.18, 2.49)], suggesting that the body’s omega-3 content was indeed replenished but did not change the patient’s depressive state; analyzed by different courses of therapy, a 10-week course of therapy [SMD=0.02 (95% CI: -0.23, 0.26)] and a 12-week course of therapy [SMD=0.40 (95% CI: -0.40, 1.20)] both resulted in a lack of improvement in depressive symptoms. Conclusion According to the available evidence, omega-3 PUFAs do not alleviate anxiety or depression in coronary artery disease patients. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023391259.